2020
DOI: 10.1016/j.jinorgbio.2019.110907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, DNA binding, topoisomerase inhibition, and apoptosis induction studies of a novel cobalt(III) complex with a thiosemicarbazone ligand

Abstract: × 10 5 and 1.6 × 10 4 M −1 , respectively). Topoisomerase inhibition assays and cleavage studies proved that complex 4 was an efficient catalytic inhibitor of human topoisomerases I and IIα. Based upon the results obtained from the 3-(4,5-dimethylthiazol-2-yl)-5-(3carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay on 4T1-luc metastatic mammary breast cancer cells (IC 50 = 34.4 ± 5.2 μM when compared to IC 50 = 13.75 ± 1.08 μM for the control, cisplatin), further investigations into the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 230 publications
(280 reference statements)
1
7
0
Order By: Relevance
“…The coordination configurations of these Ru(II) complexes are similar to those of the mixed ligand Co(III) complexes of 9-anthrahydrazone and o -phenanthroline/bipyridine, as previously reported by Alvin A. Holder et al [ 119 ]. Competitive fluorescence analysis of DNA and DNA viscosity experiments conducted using ethidium bromide (EB) as a probe showed that the two Ru(II) complexes bind to DNA via intercalation with a strong binding ability.…”
Section: The Anticancer Activity Studysupporting
confidence: 83%
See 2 more Smart Citations
“…The coordination configurations of these Ru(II) complexes are similar to those of the mixed ligand Co(III) complexes of 9-anthrahydrazone and o -phenanthroline/bipyridine, as previously reported by Alvin A. Holder et al [ 119 ]. Competitive fluorescence analysis of DNA and DNA viscosity experiments conducted using ethidium bromide (EB) as a probe showed that the two Ru(II) complexes bind to DNA via intercalation with a strong binding ability.…”
Section: The Anticancer Activity Studysupporting
confidence: 83%
“…Alvin A. Holder’s team [ 118 , 119 ] also attempted to synthesize a novel vanadium(IV) complex and cobalt(III) complex of 9-anthrahydrazone with methyl thiourea as a side chain by introducing different co-ligands ( Figure 39 ). In 2012, they reported the synthesis of a lead complex with tryptophan, salicylic acid, and VOSO 4 and further mix-coordinated with the above 9-anthrahydrazone ligand to synthesize a new V(IV) complex as well as two other V(IV) complexes of non-anthrahydrazone ligands.…”
Section: The Anticancer Activity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…where [DNA] refers to DNA concentration and ε a , ε b and ε f represent apparent, fully bonded, and free molar extinction coefficients of the peptide, respectively [64][65][66]. The Wolf-Shimer plots, using absorbance of the peptide at 257 nm vs. CT-DNA and gDNA-1gDNA2 concentration, is shown in Figure 4.…”
Section: Electronic Absorption Spectramentioning
confidence: 99%
“…Topoisomerases are enzymes implicated in DNA replication during cell division. They are upregulated in cancer cells and are, therefore, the targets of anticancer drugs (Azarova et al, 2007; Beebe et al, 2019; Pommier, 2013; Wang, 2002). Clinically successful anticancer agents, such as doxorubicin and camptothecin, act through the poisoning of topoisomerases, leading to the formation of double‐strand break and ultimately replication fork arrest (Amin, Gali‐Muhtasib, Ocker, & Schhneider‐stock, 2009; Delgado, Hsieh, Chan, & Hiasa, 2018; Irfan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%